More treatment but no less depression: The treatment-prevalence paradox. (February 2022) - Ormel, Johan; Hollon, Steven D.; Kessler, Ronald C.; Cuijpers, Pim; Monroe, Scott M.
Abstract: Treatments for depression have improved, and their availability has markedly increased since the 1980s. Mysteriously the general population prevalence of depression has not decreased. This "treatment-prevalence paradox" (TPP) raises fundamental questions about the diagnosis and treatment of depression. We propose and evaluate seven explanations for the TPP. First, two explanations assume that improved and more widely available treatments have reduced prevalence, but that the reduction has been offset by an increase in: 1) misdiagnosing distress as depression, yielding more "false positive" diagnoses; or 2) an actual increase in depression incidence. Second, the remaining five explanations assume prevalence has not decreased, but suggest that: 3) treatments are less efficacious and 4) less enduring than the literature suggests; 5) trial efficacy doesn't generalize to real-world settings; 6) population-level treatment impact differs for chronic-recurrent versus non-recurrent cases; and 7) treatments have some iatrogenic consequences. Any of these seven explanations could undermine treatment impact on prevalence, thereby helping to explain the TPP. Our analysis reveals that there is little evidence that incidence or prevalence have increased as a result of error or fact (Explanations 1 and 2), and strong evidence that (a) the published literature overestimates short- and long-term treatment efficacy, (b) treatments are considerably less effective as deployed in "real world" settings, and (c) treatment impact differs substantially for chronic-recurrent cases relative to non-recurrent cases. Collectively, these a-c explanations likely account for most of the TPP. Lastly, little research exists on iatrogenic effects of current treatments (Explanation 7), but further exploration is critical. Highlights: The puzzling paradox of more treatment but no less depression requires answers. First incidence has probably not increased and offset treatment-driven prevalence drops. The published trial literature substantially overestimates efficacy of treatments. In addition, treatment-quality gaps in routine care reduce effectiveness further. Longterm outcome, undertreatment of recurrence, iatrogenicity need further study.